Epitaxial growth on 4H-SiC by TCS as a silicon precursor - 纪刚 孙国胜 刘兴昉 王雷 赵万顺 曾一平 李晋闽 (Journal of semiconductors, 2009)
Epitaxial growth on n-type 4H-SiC 8° off-oriented substrates with a size of 10 × 10 mm^2 at different temperatures with various gas flow rates has been performed in a horizontal hot wall CVD reactor, using trichlorosilane （TCS） as a silicon precursor source together with ethylene as a carbon precursor source. The growth rate reached 23 μm/h and the optimal epilayer was obtained at 1600℃ with a TCS flow rate of 12 sccm in C/Si of 0.42, which has a good surface morphology with a low RMS of 0.64 nm in an area of 10 x 10 pm2. The homoepitaxial layer was obtained at 1500℃ with low growth rate （〈 5 μm/h） and the 3C-SiC epilayers were obtained at 1650 ℃ with a growth rate of 60-70 μm/h. It is estimated that the structural properties of the epilayers have a relationship with the growth temperature and growth rate. Silicon droplets with different sizes are observed on the surface of the homoepitaxial layer in a low C/Si ratio of 0.32.